Gastric precancerous conditions or lesions and Helicobacter pylori - M Areia; M. Dinis-Ribeiro (Microbiota in Health and Disease)
Gastric cancer is one of the most common malignancies and a leading cause of mortality worldwide, mainly caused by Helicobacter pylori (H. pylori).